RESEARCH ON CONTACT DAMPING CHARACTERISTICS OF JOINT SURFACE OF MICRO TEXTURED SURFACE - ZHU ChunXia; LIU Lei; ZHAO Yuan; WANG Ning (Jixie qiangdu)
The effect of surface morphology parameters on the contact damping of miero textured surface was studied. The damping source of the joint surface is analyzed, and the mathematical model of the damping of a single micro convex body on the joint surface is established. Further, based on the distribution density function of planar micro bumps, the number of surface contact micro bumps is calculated, and the effects of texture density, material characteristic parameters, frequency and amplitude of applied dynamic load on contact damping are studied. The results of research and example analysis show that the higher the texture density is, the smaller the contact damping between the surfaces is. With the increase of material characteristic parameters, the normal contact damping increases. With the increase of vibration frequency, the contact damping decreases gradually under the same load. The larger the dynamic deformation amplitude is, the greater the contact damping is.